EARNING MANAGEMENT EFFECT ON FINANCIAL STATEMENT FRAUD, WITH CORPORATE GOVERNANCE AS A MODERATING VARIABLE - Widanarni Pudjiastuti; Fera Tjahjani; Nanda Alivia Pratikasari; Bunyamin Bunyamin (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study aims to explore the role of corporate governance as a moderating variable on the effects of earning management on financial statement fraud. The purposive sampling method was used to obtain 37 manufacturing multinational companies from Indonesia Stock Exchange (IDX) for the years 2018 – 2020. Moderated Regression Analysis (MRA) technique was used to test the Beneish M-score model. Earning management is proxied by discretionary accrual, and corporate governance is proxied by independent commissioners, managerial ownership, institutional ownership, and audit committee financial expertise. Earning management has a positive significant effect on financial statement fraud and audit committee financial expertise strengthens the effect of earning management on financial statement fraud. Meanwhile, independent commissioner, managerial ownership, and institutional ownership could not moderate earning management to financial statement fraud. The audit committee variable strengthened the relationship between earnings management and financial statement fraud, therefore, for further research employ the ethics of the audit committee as an additional variable.